Pendidikan Moral dalam Keluarga Modern: Perspektif Ekologi Sosial - Fatchurrohman Fatchurrohman (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2012)
Modernization, in fact, brings negative effect, i.e., the degradation of human values such as mechanization of human life. Humans have no more freedom. Technological values with their own calculation substitute human values. Capitalistic materialism unintentionally also brings the global advancement and parasitically infiltrates the human life. As the consequence, the moral relation among human being, environment and God also changes. In this condition, family takes a strategic role to fortify and solve the problem of children moral crisis. To solve the children moral crisis, the family needs to recognize some factors of the moral and behavior of the children and makes some efforts to control or demolish the pioneering factors affecting the negative behavior of children. The family should pay more attention to several influential elements such as climate in the family, school selection, peers, selection of mass media programs (television and radio), information and technology (hand phone and internet), and the condition of social environment.